Low-maintenance subtropical green roofs. Spontaneous vegetation and substrate deph - Brenda Chaves Coelho Leite; Lucas Gobatti; Isabela Gamba Huttenlocher (Agathón)
Spontaneous and ruderal plants can be the key to a low-cost, low-maintenance urban Green Infrastructure that can adapt to the local climate context. In addition to providing a wide range of Ecosystem Services, such species can survive in environments altered by humans and withstand conditions adverse to them, such as water scarcity and shallow substrate. The paper aims to systematically identify the effects exerted by substrate depth during the first months of vegetation growth using the Point-Intercept method in low-maintenance extensive green roofs. Contrary to previous research focusing on vegetation growth in temperate climates, experimentation in a humid subtropical climate can help to fill a gap by assessing the long-term potential of roofs with heterogeneous spontaneous species establishment to improve urban ecology and its natural regeneration.